Online Blade Washing Analysis on Mitsubishi M701F Gas Turbine Performance in Power Plants - Wilarso; Ari Dwi Wibowo (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2021)
The main problem that often occurs in the operation and maintenance of power plants is a decrease in the reliability of the Gas Turbine. The decline in the performance of the Gas Turbine, which often experiences trips, was recorded at the highest 3 times in one day. Based on the inspection, it was found that there were deposits on the compressor and turbine blades during operation. The decrease in power in the generating unit is accompanied by an increase in fuel consumption. The purpose of this study is to analyze Blade Washing Online on the performance of gas turbines due to the formation of carbon deposits on the compressor wheel and turbine wheel. To improve the reliability of the gas engine, a method of doing Blade Washing is needed to clean carbon deposits in the compressor and turbine wheel. Based on the results of research before Blade Washing the turbine power only reached 255.37621 MW, after Blade Washing was able to make the compressor work more reliably, produce good turbine gas efficiency, and be able to reduce turbine gas performance disturbances due to running hours the power generated reached 268,77738 MW, there is a fuel consumption savings of 1.4 kg/s and thermal efficiency of 0.8%. In the Tanjung Priok Block 3 PLTGU unit, Online washing is carried out at a load condition of 200MW ±5MW. To clean fouling and maintain the performance of the turbine. Cleanliness of the compressor and turbine blades can be maintained by carrying out this blade washing based on a periodic schedule calculated based on running hours.